Ways of coping of prisoners’ spouses: a structural equation model - Insong, Junvil A.; Cuevas Jr., Jose F. (Technium Social Sciences Journal, 2021)
The study is intended to determine and offer the best fit model in the ways of coping of prisoners’ spouses. It explored the interrelationships of variables, including the level of psychological well-being, social support, and distress tolerance on ways of coping on prisoners’ spouses. It is a quantitative research design and structural equation modeling. Data were from 400 prisoners’ spouses in Misamis Occidental Region X. The questionnaire was divided into four sections: psychological well-being, social support, distress tolerance, and coping methods. Results showed that the respondents’ psychological well-being, social support, and distress tolerance were all high levels. High levels also resulted in ways of coping of prisoners’ spouses. Moreover, results showed that the relationships between psychological well-being, social support, and distress tolerance to ways of coping of prisoners’ spouses were all significant. It means that an increase in the level of psychological well-being increases social support, distress tolerance, and the level of coping of the respondents. The conclusive statement drawn includes that the very high level of social support, high levels of psychological well-being and distress tolerance, and coping mechanisms of prisoners’ spouses are significantly related.